A constitutive model for modified cable bolts exhibiting cone shaped failure mode. (September 2021) - Li, Danqi; Cai, Ming; Masoumi, Hossein
Abstract: This study presents a novel constitutive model to characterise the mechanical behaviour of cable bolts under axial loading and subjected to different boundary conditions including constant confining pressure and constant normal stiffness. Such a model is developed based on the modified Mohr-Coulomb failure criterion as well as a newly proposed non-linear dilation formulae for the development of governing equations. The cone shaped failure mode of grout due to the axial movement of cable bolt is considered as a widely observable failure mode at the cable bolt to the grout interface. The load carrying capacity of the cable bolt under axial loading is significantly affected by both the progressive reduction in the volume of failed cone zone of grout annulus and the continuous degradation of dilation angle at the cable bolt to the grout interface. Hence, the full load-displacement performance of different cable bolts under axial loading subjected to both constant confining pressure and constant normal stiffness are simulated. Finally, an acceptable agreement between the model simulations and the experimental data confirms the credibility of proposed constitutive model for predicting the mechanical behaviour of different cable bolts under axial loading.